The Role of Arthroereisis in Improving Sports Performance, Foot Aesthetics and Quality of Life in Children and Adolescents with Flexible Flatfoot - Alexandru Herdea; Adrian-Gabriel Neculai; Alexandru Ulici (Children, 2022)
Flexible flatfoot represents one of the most common deformities of the lower limb, affecting children and adolescents. Aesthetic aspect, abnormal gait, pain and fatigue are by far the most important symptoms which determine parents to bring their children to the orthopedist. We set out to conduct a prospective study, case-controlled, including patients with symptomatic flexible flatfeet operated on by arthroereisis surgery and comparing them to a normal feet group of children age- and sex-matched (control group). Minimum follow-up time was 2 years. In total, 33 patients with bilateral arthroereisis were included and 36 patients formed the control group (12.12 +/− 1.85 years vs. 11.81 ± 2.40 years, p = 0.54). Quality of life improved postoperatively (p = 0.18) and was not different from the control group. Median running time improved postoperatively by 2.25 s (p < 0.0001) and got closer to the median running time from the control group (22.30 s compared to 20.94 s, p = 0.01). All radiological angles improved (p < 0.0001), but quality of life improvement was correlated with talonavicular coverage angle and Meary angle measurements. Flatfoot in children and adolescents may be a condition in which the quality of life and sports performance are decreased, compared to healthy children. Arthroereisis is a minimally invasive surgical procedure with a short recovery time and a short period before resumption of sport activities, which can be useful in certain types of flexible flatfoot due to its effectiveness on symptom reduction.